معوقات تطبيق التعليم عن بعد في الجامعة الجزائرية - حوامدي, نجاح; رحال, هاجرة (جامعة الوادي - University of Eloued, 2023)
The study aimed to explore the obstacles to the application of distance education in the Algerian university from the point of view of the professors of a sample of the professor of the Faculty of Social and Human Sciences at the University of Echahid Hama, Lakhdar EL-OUED. The study sample included (60) professors from the faculty, and the research questionnaire was applied, and the descriptive approach was followed for its suitability to the nature of the study, then the researcher used the arithmetic mean, standard deviation, ANOVA, and T test to study the differences, and after drawing the results, the following was reached: *The formative aspect of the professor constitutes an obstacle to the application of distance education in the Algerian university. *The formative aspect of the professor constitutes an obstacle to the achievement of distance education in the Algerian university. *The professor's relationship with the student is an obstacle to achieving the goals of the study. *The technical side is a hindering factor for distance education. *The relationship with the administration is a factor for the success of distance education. *There are differences between the respondents in the study sample regarding the obstacles to the application of distance learning due to the gender variable, where the significance level of the T values for these variables was less than ( 0.05 .) *That there are no differences between the respondents in the study sample for the obstacles to the application of distance learning due to the personal and functional variables (educational rank, computer use efficiency), where the significance level of the F values for these variables was greater than ( 0.05 .) *There are differences between the respondents in the study sample regarding the obstacles to the application of distance learning due to the variable years of experience, where the significance level of the F values for these variables was less than (
مذكرة ماستر علم اجتماع تربية